The Implementation of an Information Service with Android-Based Career Card Medium to Improve Students' Understanding of Career Planning - Rahmawati, Riska Novia; Sugiyo, Sugiyo; Sutoyo, Anwar (Universitas Negeri Semarang, 2022)
A common obstacle in career planning is the lack of further study information. Therefore, the present study aimed at improving students’ career planning using an information service with android-based career card medium. To do so, it used a one-group pretest-pottest design. Further, the instrument used to collect the data was a career planning understanding scale. It was given to 30 grade eleven students selected from 427 students using a purposive random sampling technique. Findings showed an improvement of students’ career planning following the use of an information service with android-based career card medium. Moreover, schools can provide career information services for students since the very beginning of their school lives so that they can get some overviews of university lives.